2002
DOI: 10.1046/j.1468-2982.2002.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Cgrp May Play A Causative Role in Migraine

Abstract: Calcitonin gene-related peptide (CGRP) has been detected in increased amounts in external jugular venous blood during migraine attacks. However, it is unknown whether this is secondary to migraine or whether CGRP may cause headache. In a double-blind crossover study, the effect of human alphaCGRP (2 microg/min) or placebo infused intravenously for 20 min was studied in 12 patients suffering from migraine without aura. Headache intensity was scored on a scale from 0 to 10. Two patients were excluded due to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
713
1
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 897 publications
(776 citation statements)
references
References 29 publications
30
713
1
15
Order By: Relevance
“…CGRP is believed to play an important role in the genesis and maintenance of inflammation and pain associated with both migraine and TMJ pathology (Lassen et al, 2002;Juhasz et al, 2003;Lobbezoo et al, 2004). In this study, we used an in vivo model of TMJ inflammation to investigate the effect of Theobroma cacao extract on trigeminal nerve activation and CGRP release.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is believed to play an important role in the genesis and maintenance of inflammation and pain associated with both migraine and TMJ pathology (Lassen et al, 2002;Juhasz et al, 2003;Lobbezoo et al, 2004). In this study, we used an in vivo model of TMJ inflammation to investigate the effect of Theobroma cacao extract on trigeminal nerve activation and CGRP release.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma concentrations of CGRP, but not of SP, were elevated during the headache phase of migraine [64] and cluster headache [65]. There is evidence that intravenous infusion of CGRP produces a migraine-like headache [66], and intravenous infusion of nitric oxide produces a migraine-like headache with an associated increase in plasma CGRP levels [67]. In migraine patients baseline CGRP levels were considerably higher, and the changes in plasma CGRP levels during migraine attacks were significantly correlated with the headache intensity [67].…”
Section: Migraine and Neurogenic Inflammationmentioning
confidence: 99%
“…Elevated levels of CGRP, but not of other neuropeptides, were found in the external jugular vein during the headache phase of migraine and normalized in parallel with headache improvement [22,23]. Furthermore, infusion of human CGRP was found to trigger a migraine attack in susceptible individuals, while normalization of CGRP levels were obtained after migraine treatment with triptans [24][25][26]. These findings provided new insight into a putative role of CGRP in the pathophysiology of migraine, opening new pathways for therapeutic intervention.…”
Section: Pathophysiologymentioning
confidence: 81%
“…Positron emission tomography (PET) imaging studies in healthy subjects and migraineurs demonstrated that CGRP-RAs do not act centrally [104]. Similarly, intravenous administration of CGRP can induce migraine in susceptible individuals without crossing the BBB [24]. Antibodies consist of larger size molecules that are even less likely to cross the BBB.…”
Section: Blood-brain Barriermentioning
confidence: 99%